Cancel Culture in the Frame of Comparison of Indonesia and South Korea - Anjarini, Dipta Ninggar (Universitas Negeri Semarang, 2020)
Cancel culture is a culture that is carried out by the community in the form of canceling or retaking its support for an object of publik consumption or influencer after it is deemed to have violated the norms applicable in society. This study comparing comprehensively the cancel culture in Indonesia and South Korea. The research was carried out using the literature study method by exploring theoretical references that were relevant to the research subject or problems that would be discussed further. The result of this study reveals that the intensity and the implementation of cancel culture has a significant impact to the effectiveness of social control. ‘cancel culture’ is often used as an excuse to reject other people's opinions that are different from the opinions of the netizen. Therefore, further research is needed on the implementation of cancel culture in Indonesia, accompanied by good quality digital literation competencies, so that cancel culture is not only used as an excuse to convey hate comments but also provides a deterrent impact and social sanctions for public figures who are being ‘cancelled’ by the community.